An improved method of active earth pressure on rigid retaining wall under movement modes considering arching effects. (12th December 2022) - Fan, Ling; Zheng, Zhuyan; Peng, Shuquan; Zhou, Jian; Shen, Tianli; Wan, Hua; Ma, Hongling
Abstract: Both wall movement mode and soil arching are important to the active earth pressure on rigid retaining wall, but the method of active earth pressure under wall movement modes considering arching effects is yet to be studied. A series of minor principal stress trajectories described by the power function with the exponent b is assumed to analyze the soil arching effect using the equivalent friction coefficient between adjacent soil layers. The horizontal Winkler elastic foundation beam model induced by wall movement modes is presented. Then based on the trajectories and wall movement modes the horizontal flat‐element method of active earth pressure on rigid retaining wall is improved and verified. The active earth pressures on the retaining wall under translation (T), rotation about top (RT) mode and rotation about bottom (RB) mode calculated by the improved method are in a better agreement with the experimental results than other analytical studies. The application point of the resultant active earth pressure on retaining wall increases from 0.25 H to 0.49 H with varies of wall movement modes considering soil arching effect. The larger equivalent friction coefficient is, the more notable soil arching effect is. The most notable soil arching effect is described by the approximate linear minor principal stress trajectory whose power function with exponent of b approaches zero from positive direction. The active earth pressure on retaining wall under RT mode considering the most notable soil arching effect is simplified and suggested for the engineering practice.